Relasi Agama dan Moralitas Masyarakat Postsekular Negara: Telaah atas Pemikiran Juergen Habermas - Otto Gusti Madung (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
The resurrection of religions was back felt since the early 90s. Even, the philosophy that overshaded under jargon “post-metaphysical” began to take an interest in religious issues. Juergen Habermas who called himself “religioes unmusikalisch” (not religiously gifted) made the relationship between religion and rationality in post-secular society as a main theme of his philosophical studies in recent years. Habermas built his theory upon Kantian’s thesis and criticized Kant who did not give a clear line of demarcation between religion and reason. By using an analytical tool of Schleichermacher and Derrida, this paper rejects the Habermas’ thesis and shows the close relationship between faith and reason. This paper uses method of literature research by referring to the Germanic original works of Habermas and some comments on it.